(untitled) (Ghana Journal of Science, Technology and Development, 2024)
Traditional African Vegetables (TAV) are widely grown and consumed in northern Ghana, providing essential micronutrients for a healthy diet. This study sought to identify factors that influence the frequency with which rural households consume vegetables. Cross-sectional data from 187 rural households were collected and analysed using the Poisson count regression model. A 6-item dietary assessment tool from the 2017 Behavioural Risk Factor Surveillance System (BRFSS) was used to measure the frequency of vegetable consumption. The results of the study revealed that socioeconomic factors such as the caregiver’s age, household wealth status, household dietary diversity, occupation of the household head, and household food security status influenced the frequency of vegetable consumption. Therefore, future campaigns to improve vegetable consumption should prioritise economic characteristics associated with the household head and household. Moreover, cost, availability, and access are important factors to consider when promoting household vegetable intake in rural areas. Keywords: traditional African vegetable, vegetable intake, vegetable consumption, Rural, Ghana